PENINGKATAN KUALITAS UDARA MELALUI PENATAAN RUANG TERBUKA HIJAU (RTH) DENGAN TANAMAN PEMBERSIH UDARA - Anou, Kezia N.; Radjabaycolle, Flinn C.C.; Sinaga, Ego S.; Ngaderman, Hubertus; Rahman, Rahman; Napitupulu, Daniel; Tabuni, Wani (JURNAL PENGABDIAN PAPUA, 2024)
The corona virus which is endemic in all parts of the world, including Indonesia, has not only left a negative impact but also brought people into good habits. One of them is increasing concern for the cleanliness of the air inside and outside the place of activity. The location of the GIDI Efata Kotaraja building is located in a densely populated residential area and busy traffic causes the surrounding air to become very hot and dusty. Green plants or trees that can block dust arising from household activities and motorized vehicles are very lacking in the church yard. By looking at the surrounding environmental conditions which do not support clean air circulation, there is great concern that the air circulation in the church room will become unhealthy. Air purifier as air cleaning devices are very unaffordable. Just installing an Air Conditioner (AC) is also not enough to guarantee that the air is free from pollutants. Dust with very small particle sizes, CO2 gas and CO gas and other gases can threaten the health of congregation members. It is for this reason that this service activity has been carried out. An innovative, environmentally friendly and economical solution is needed to create good air by planting the ornamental plants Mother-in-law's Tongue, Paris Lilies and Gading Siri which have been proven to be able to absorb pollutants. The aim of this service activity is to create Green Open Space by providing outreach regarding air pollution, types of pollutants and their impact on health, providing information and knowledge related to innovative research on air cleaning plants, providing assistance in planting air cleaning plants, planting methods and techniques care for the young GIDI group of the Efata Kotaraja Congregation. The method used in this service activity is the 3P method (Counseling, Guidance and Mentoring). The result of this activity is an innovative product in the form of a park as a green open space. The conclusion that the youth have experienced an increase in knowledge and are able to realize the creation of green open space and have a culture of loving the environment.